Green Investing, Environmental Performance, and Firm Valuation: Evidence from Indonesia - Diantini , Ni Nyoman Ayu; Darmayanti, Ni Putu Ayu; Candraningrat, Ica Rika (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study investigates how green investing influences a firm environmental performance and eventually affects its financial valuation. Little research has addressed whether green investing can affect corporate environmental performance and how it influences the firm value, specifically when looking into its channels. Using companies listed on the Indonesia Stock Exchange from 2009 to 2021 and a pooled OLS on unbalanced panel data, our results suggest that green investing significantly enhances the company’s environmental performance. The positive relationship between green investing and environmental performance is strengthened if the company is involved in social investment forums, while a firm with high shareholder protection weakens the positive relation. Further, the results show that environmental performance lowers the firm value. However, suppose firms focus on green innovation to develop and conduct eco-friendly research where economic value and environmental sustainability can be carried out simultaneously. In that case, it leads to higher firm financial performance. We extend the literature by contributing to the fields of investment management, innovation, and environmental literature by emphasizing financial logic that prioritizes the welfare of shareholders, which can be an important instrument to support the environmental logic of green investing.